The lighthouse keeper's rescue - Armitage, Ronda; Armitage, David (London : Scholastic, 2001)
Everyone forgives Mr. Grinling, the lighthouse keeper, and his forgetfulness, after he organizes a whale rescue.
2.5
K-3.
K-3
Keywords: Lighthouses -- Fiction; Lighthouses -- Fiction